Experimental evaluation of affective embodied agents in an information literacy game - Guo, Yan Ru; Goh, Dion Hoe-Lian; Bin Hussain Muhamad, Hurizan; Ong, Boon Kuang; Lei, Zichao (JCDL '16 : proceedings of the 16th ACM/IEEE-CS Joint Conference on Digital Libraries : June 19-23, 2016, Newark, NJ, USA, 2016)
Digital game-based learning (DGBL) has become increasingly popular. With elements such as narratives, rewards, quests, and interactivity, DGBL can actively engage learners, stimulating desired learning outcomes. In an effort to increase its appeal, affective embodied agents (EAs) have been incorporated as learning companions or instructors in DGBL. However, claims about the efficacy of using affective EAs in DGBL have scarcely been subjected to empirical analysis. Therefore, this study aims to investigate the influence of affective EAs on students' learning outcome, motivation, perceived usefulness, and behavioral intention in an information literacy (IL) game. Eighty tertiary students were recruited and randomly assigned in a pre- and post-test between-subjects experiment with two conditions: affective-EA and no-EA. Results showed that participants benefited from interacting with the affective EA in the IL game in terms of attention, confidence, satisfaction, and intention to learn IL knowledge and to recommend. However, there were no significant differences in learning outcome, relevance, or intention to play the game. Contributions and limitations of this study are also discussed at the end.